The Impact of Contextual Factors on the Decision to Imprison in large Urban Jurisdictions: A Multilevel Analysis - Weidner, Robert R. (Crime & delinquency, 2005)
This study examines the influence of social and legal contextual factors on the processing of individual felony cases in large urban jurisdictions for 1998. Results of hierarchical logistic regression analyses that control for the effects of individual case-level factors show that three jurisdictional characteristics-use of sentencing guidelines, level of crime, and racial composition-influence the decision to imprison. These findings suggest that the type of sentence one receives and the reason one receives it partially depend on where it is meted out. This research demonstrates the importance of accounting for case-level factors in studies of cross-jurisdictional differences in punitiveness. [ABSTRACT FROM AUTHOR]